Phase composition and structure of multilayered coatings of Ni-Al system; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Fedorischeva M. V. Marina; Sergeev V. P. Viktor Petrovich; Kalashnikov M. P. Mark Petrovich; Voronov A. V. Andrei; Bozhko I. A. Irina Aleksandrovna (2014, 2014)
Title screen